A Case Study On Property Developer Company Sunrise Berhad - Lau, Hoong Chew (2006)
This case study paper diagnoses Sunrise's internal and external environments of the company and benchmarking Sunrise's performance versus its industry competitors. In addition, this study also seeks to evaluate business strategies that Sunrise employs and outline strategic plans that are required to reposition itself in strive to maintain competitiveness, sustaining growth and thus generating greater profits.